Sodium azide ingestion and secondary contamination risk in healthcare workers. (February 2016) - Downes, Michael A.; Taliana, Katrina E.; Muscat, Tracy M.; Whyte, Ian M.
Abstract : This study reports the follow-up of healthcare staff directly involved in managing a fatal sodium azide ingestion. Clinical staff directly involved with the case were contacted by telephone or in person. Data collected were age, sex, time in contact with the patient, time off work following the incident and whether or not this was because of physical complications of exposure. Ten individuals had close contact with the case. Of these, five were men, median age was 39 years (range 22–52); four described being in close contact for greater than 60 min, three for 15–60 min and three for 5–15 min. Absence from work occurred in two cases for 1 day and several weeks, neither attributed to the physical effects of exposure. Our data do not support close contact with a sodium azide ingestion case as posing a high risk of significant postexposure complications in emergency service workers.